The role of the emergency medicine resident using the Alvarado score in the diagnosis of acute appendicitis compared with the general surgery resident - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2003)
Purpose: To compare the accuracy of diagnosing appendicitis between emergency medicine residents using the Alvarado score and general surgery residents using ultrasonography and their clinical provision. Methods: A total of 358 patients (192 men and 166 women) were admitted to the emergency service with suspected appendicitis. Each patient was evaluated by an emergency medicine resident and then by a general surgeon independently. Age, sex, operational data, diagnosis, and the Alvarado scores were measured. Results: The sensitivity and specificity of the Alvarado score were 95.4% (95% confidence interval 91-99%) and 45.7% (95% confidence interval 37.4-54%), respectively. There was a significant difference between the sexes in the predictive values of a positive test (P = 0.045) and a negative test (P = 0.02). There was no statistical difference between the emergency medicine residents and general surgery residents in terms of positive and negative predicitive values (P>0.05 each). Conclusion: There was no statistical difference between the emergency medicine residents using the Alvarado score and the general surgery residents in terms of suspecting the diagnosis of appendicitis. (c) 2003 Lippincott Williams & Wilkins.
Keywords: Acute appendicitis; Alvarado score; emergency medicine resident; ultrasonography; COMPUTED-TOMOGRAPHY; CLINICAL-ASSESSMENT; ULTRASONOGRAPHY; IMPROVE